Investigating Predictive Factors of Power of the Theory Planned Behavior (TPB) on the Prevention of Urinary Tract Infection in Mothers Under 2 Years of Age - Zahra Ahmadi; Mohsen Shamsi; Nasrin Roozbahani; Rahmatalah Moradzadeh (Hamadan University of Medical Sciences, 2019)
Introduction: One of the most important problems in childhood is urinary tract infections, which can lead to permanent damage to the kidneys. The purpose of this study was to measure the constructs of the theory of planned behavior regarding the preventive behaviors of urinary tract infection in mothers with a dughter under two years of age. Methods: This is a cross-sectional and analytical study that was carried out on 280 mothers of girls under the age of two years who referred to health centers and were randomly selected. The data was collected by a researcher-made questionnaire validity and reliability of which were confirmed. The questionnaire included demographic characteristics of the mother, dimensions of the planned behavioral model and maternal duty checklist. Finally, the data were analyzed using SPSS 20, Pearson correlation and linear regression tests. Results: Mean and standard deviation of attitude score (3.87±0.37), subjective norm (4.09±0.49), perceived behavior control (4.32±0.47), behavioral intention (4.59±0.47) performance (2.78±0.58) and knowledge (0.62±0.1) was observed. In regression analysis, variables of knowledge and intention to behave, predicted a total of 15% (R2=0.16, B=1.342, P=0.001) of behavioral change. Conclusion: According to the results of the study, in designing educational interventions, the awareness and structure of behavioral intention should be considered as the most important predictor of mothers' behavior.